Heterotrophic Bacterioplankton Growth and Physiological Properties in Red Sea Tropical Shallow Ecosystems With Different Dissolved Organic Matter Sources - Silva, Luis; Calleja, Maria Ll.; Huete-Stauffer, Tamara M.; Ivetic, Snjezana; Ansari, Mohd I.; Viegas, Miguel; Morán, Xosé Anxelu G. (Frontiers in Microbiology, 2022)
Despite the key role of heterotrophic bacterioplankton in the biogeochemistry of tropical coastal waters, their dynamics have been poorly investigated in relation to the different dissolved organic matter (DOM) pools usually available. In this study we conducted four seasonal incubations of unfiltered and predator-free seawater (Community and Filtered treatment, respectively) at three Red Sea coastal sites characterized by different dominant DOM sources: Seagrass, Mangrove, and Phytoplankton. Bacterial abundance, growth and physiological status were assessed by flow cytometry and community composition by 16S rRNA gene amplicons. The Seagrass site showed the highest initial abundances (6.93 ± 0.30 × 105 cells mL–1), coincident with maximum DOC concentrations (>100 μmol C L–1), while growth rates peaked at the Mangrove site (1.11 ± 0.09 d–1) and were consistently higher in the Filtered treatment. The ratio between the Filtered and Community maximum bacterial abundance (a proxy for top-down control by protistan grazers) showed minimum values at the Seagrass site (1.05 ± 0.05) and maximum at the Phytoplankton site (1.24 ± 0.30), suggesting protistan grazing was higher in open waters, especially in the first half of the year. Since the Mangrove and Seagrass sites shared a similar bacterial diversity, the unexpected lack of bacterial response to predators removal at the latter site should be explained by differences in DOM characteristics. Nitrogen-rich DOM and fluorescent protein-like components were significantly associated with enhanced specific growth rates along the inshore-offshore gradient. Our study confirms the hypotheses that top–down factors control bacterial standing stocks while specific growth rates are bottom-up controlled in representative Red Sea shallow, oligotrophic ecosystems.